The effectiveness of internal cohesion psychotherapy in treating young clients with depression and anxiety disorders: The role of developmental assets in Kosovo context - Uka, Fitim; Gashi, Shkumbin; Gashi, Arlinda; Gllogu, Diellza; Musliu, Arian; Krasniqi, Albina; Statovci, Albina; Sopjani, Vanesa; Perçuku, Veronë; Sadikovic, Irma; Wiium, Nora (Frontiers in Psychology, 2022)
The Positive Youth Development Approach (PYD) is widely used as a meaningful framework to guide research, policy, and intervention, to support young people to develop their full potential. Psychotherapy, on the other hand, is a verbal and psychological procedure that can be a suitable solution to mental health concerns, which are prevalent among youth. This study aimed to explore the potential role of developmental assets in treating clients with depression and anxiety disorders using Internal Cohesion Psychotherapy (ICP). In total, 10 young people who took at least five sessions of ICP were part of this study. In-depth semi-structured interviews were conducted to gather information about clients’ experiences with ICP and their perceptions/opinions on the presence of developmental assets in their lives. The results confirm the effectiveness of ICP in treating depression and anxiety, while clients acknowledge the role of developmental assets in their psychotherapeutic process. The study provides evidence on how clients use their developmental assets in maximizing the effectiveness of the ICP process, which opens a new path for intervention on mental health among youth.